(untitled) (Physical Education, Health and Social Sciences, 2025)
In the present study an approach was made to produce functional probiotic ice cream by using the four probiotic organisms namely type-1 (Sterptococcus thermophilus), type-2 (Lactobacillus bulgaricus), type-3 (Bifidobacteria), type-4 (Saccharomyces), type-5 (Mixture of Streptococcus thermophilus, Lactobacillus bulgaricus, Bifidobacteria and Saccharomyces and type-6 (Plain ice cream; without probiotic organisms) using conventional ice cream-making method. All types were assessed for proximate and rheological analysis. Total solids and carbohydrate contents were found slightly high (P<0.05) in type-III and low in type-IV; whereas in other types non-significant variation was noted. Fat content (%) was observed high in type-VI followed by IV, II, III, V and Type-I respectively. Remarkably high protein content (%) marked for the type I followed by type-II, III, IV, V and VI, respectively. Similarly, high ash content (%) was noted in Type-I and V while low in the type-II probiotic ice cream. Acidity (%) and pH value vaired among all the probiotic isecComparatively more expansion in volume (overrun %) appeared in the type III and little in type- II and VI ice cream. Type-V and I ice cream melted quickly while slowly in the type VI ice cream. On the basis of composition, rheological features, physical attributes Sacchromyces and Bifidobacterial probiotic containing types of ice cream were found better.